Transcriptome Profile and Gene Expression During Different Ovarian Maturation Stages of Macrobrachium rosenbergii (De Man, 1879) - Mohd Pauzi Mardhiyyah,; Muhammad Faiz Zakaria,; Adnan Amin-Safwan,; Mamat Nur- Syahirah,; Yeong Yik Sung,; Hongyu Ma,; Mhd Ikhwanuddin, (Tropical Life Sciences Research, 2024)
Macrobrachium rosenbergii, or giant river prawn, is the most economically crucial cultured freshwater crustacean. A predominant challenge in developing crustacean aquaculture is reproduction management, particularly ovary maturation, where identifying regulative mechanisms at the molecular level is critical. Ovary is the primary tissue for studying gene and protein expressions involved in crustacean growth and reproduction. Despite significant interest in M. rosenbergii, its gene discovery has been at a relatively small scale compared to other genera. In this study, comprehensive transcriptomic sequencing data for different maturation stages of the ovary of M. rosenbergii were observed. The 20 female M. rosenbergii samples evaluated were categorised into four maturation stages, 1 to 4. A total of 817,793,14, 841,670,70, 914,248,78 and 878,085,88 raw reads were obtained from stages 1, 2, 3 and 4, respectively. The assembled unique sequences (unigenes) post-clustering (n = 98013) was 131,093,546 bp with an average size of 1,338 bp. The BLASTX unigene search against National Centre for Biotechnology Information (NCBI), non-redundant (NR), nucleotide sequence (NT), Kyoto Encyclopaedia of Genes andGenomes Orthology (KO), Swiss-Prot, Protein Family (PFAM), Gene Ontology (GO), and euKaryotic Orthologous Groups (KOG) databases yielded 27,680 (28.24%), 7,449 (7.59%), 13,026 (13.29%), 22,606 (23.06%), 29,907 (30.51%), 30,025 (30.63%) and 14,368 (14.65%) significant matches, respectively, totalling to 37,338 annotated unigenes (38.09%). The differentially expressed genes (DEG) analysis conducted in this study led to identifying cyclin B, insulin receptor (IR), oestrogen sulfotransferase (ESULT) and vitellogenin (Vg), which are critical in ovarian maturation. Nevertheless, some M. rosenbergii ovarian maturation-related genes, such as small ubiquitin-like modifier (SUMO)-activating enzyme subunit 1, E3 ubiquitin-protein ligase RNF25, and neuroparsin, were first identified in this study. The data obtained in the present study could considerably contribute to understanding the gene expression and genome structure in M. rosenbergii ovaries throughout its developmental stage.